Lupus nephritis - alarmins may sound the alarm? - Wu, Tianfu (BioMed Central, 2012)
A growing body of literature has documented the elevated levels of the alarmin HMGB1 in lupus skin and serum. Two recent reports highlight the increased expression of HMGB1 in lupus nephritis, within the diseased kidneys or in the urine. Taken together with previous reports, these findings suggest that the interaction of HMGB1 with a variety of receptors, including receptor for advanced glycation end products (RAGE) and Toll-like receptors, might play a role in the pathogenesis of lupus nephritis. These studies introduce urinary HMGB1 as a novel biomarker candidate in lupus nephritis. Whether alarmins would be effective in sounding the alarm at the incipience of renal damage remains to be ascertained.